(untitled) (Ustozlar uchun, 2025)
The integration of technical equipment into classroom instruction has become increasingly important in modern education. Using tools such as interactive whiteboards, projectors, computers, tablets, and audio-visual devices enhances the learning process by providing visual, auditory, and interactive support. This approach not only increases student engagement but also promotes better understanding, retention, and application of knowledge. The study explores strategies for effectively incorporating technical equipment into lessons, emphasizing lesson planning, classroom management, and the development of digital literacy among both teachers and students. Additionally, it highlights the benefits of blended learning and the role of educational technologies in fostering collaborative and independent learning. By applying technical tools systematically, teachers can create a more dynamic, interactive, and motivating learning environment that addresses diverse learner needs and learning styles.